The role of lectin-like oxidised low-density lipoprotein receptor-1 in vascular pathology. (November 2014) - Shaw, Daniel James; Seese, Rachel; Ponnambalam, Sreenivasan; Ajjan, Ramzi
The lectin-like oxidised low-density lipoprotein receptor-1 (LOX-1) is a vascular scavenger receptor that plays a central role in the pathogenesis of atherothrombotic disease, which remains the main cause of mortality in the Western population. Recent evidence indicates that targeting LOX-1 represents a credible strategy for the management vascular disease and the current review explores the role of this molecule in the diagnosis and treatment of atherosclerosis. LOX-1-mediated pro-atherogenic effects can be inhibited by anti-LOX-1 monoclonal antibodies and procyanidins, whereas downregulation of LOX-1 expression has been achieved by antisense oligonucleotides and a specific pyrrole–imidazole polyamide. Furthermore, LOX-1 can be utilised for plaque imaging using monoclonal antibodies and even the selective delivery of anti-atherosclerotic agents employing immunoliposome techniques. Also, plasma levels of the circulating soluble form of LOX-1 levels are elevated in atherosclerosis and therefore may constitute an additional diagnostic biomarker of vascular pathology.